LES POLITIQUES DE DEVELOPPEMENT AGRICOLE DANS LES PAYS EN DEVELOPPEMENT - Edmond, Aïwa Aïwa (European Scientific Journal, ESJ, 2015)
Agriculture, like any other economic activities, is subjected to the effects of the general economic policy. Among these effects, there are the variations of exchange rate, the taxation, interest rate, the price ratios, etc. In this study, I will deal with some specific issues of the agricultural policy and focus on three types of agricultural policies without which there would be no possible development in agriculture. For this reason, it is particularly necessary to review the policies suggested, and to examine under which conditions they can contribute to achieve the goals assigned in order to ensure the development of a productive and competitive agriculture respectful of the environment.